Smart City Strategies in Slovak Cities - Ján MACHYNIAK; Dalibor MIKUŠ; Kristína DZUREKOVÁ; Paulína SROVNALÍKOVÁ (European Journal of Interdisciplinary Studies, 2023)
The concept of Smart City represents a resonating theme in the world, which is based on the efforts of the creators of this concept to increase the quality of life in cities. In recent years, it has gradually become a phenomenon that cities around the world are trying to apply. The reason for its introduction is the added value in the form of more efficient functioning of human society, as according to the data available so far, it increases safety in the city, enables more efficient transport of goods, services, human capital, reduces the negative impact on the environment, speeds up administrative processes, increases economic development and brings financial savings. All this is happening against the background of the increased interest of city dwellers in public administration. With these facts in mind, our ambition is to identify the degree of application of the implementation of the Smart City concept in Slovakia and, based on relevant data, create a realistic picture of the possibilities and limits of the concept in our domestic environment. In order to achieve the research objective, we rely on a set of quantitative (questionnaire survey) and qualitative methods (critical analysis) that are also used in social sciences. Based on our research intention, we must draw attention to the obviously negative state of development of this strategic concept at the level of Slovak cities. Because the Smart City concept represents a challenge for the future development of self-government in our environment, it is necessary to reflect on the current starting point and proceed with the implementation of steps aimed at correctly grasping and understanding the importance of the issue by the professional public, municipal politicians and residents of self-governing units. Due to the fact that it is a relatively new topic, there are only a few works dealing with the issue of the Smart City concept or its application in our domestic conditions. Nevertheless, our research intention is open to new knowledge and interpretations by current and future authors who find strength and interest in this issue.